The Impact of Human Resource Development (HRD) Practices on Organizational Effectiveness: A Review - Uddin, Md. Bashir; Naher, Kamrun; Bulbul, Afroza; Ahmad, Neser Aminul; Rahman, Mohammad Mizanur (Asian Business Review, 2016)
This paper attempted to review theoretically the HRD and its matrix and revealed to show the positive relationship between HRD and organizational effectiveness. In HRD shows the different variables (outcomes) such as HRD instruments, HRD processes & climate variables and organizational dimensions. HRD affects the organizational goals which may result from higher productivity, cost reduction, more profits, better image and more satisfied customers and stake holders considered as organization dimensions HRD activities, as such, do not reduce costs, improve quality or quantity, or benefit the enterprise in any way. It is the on-the- job applications of learning that ultimately can reduce costs, improve quality, and so forth. In the organizational context, therefore, HRD means a process which helps employees of an organization to improve their functional capabilities for their present and future roles, to develop their general capabilities, to harness their inner potentialities both for their self and organizational development and, to develop organizational culture to sustain harmonious superior-subordinate relationships, teamwork, motivation, quality and a sense of belongingness. The study also analyses the Kliman Model of HRM to show the path of mechanisms which could lead to competitive advantage. Today’s fast changing environment modern organizations are more careful to sustain in the competitive advantage relating to HRD our study has been developed to help the management students, academicians, and professionals to understand the subject properly and enhance their knowledge about HRD network within the organization for its effectiveness.
Keywords: HRD; Training & Development; HRD Instruments; Organizational Effectiveness